Kazimierz Twardowski: A Grammar for Philosophy - Schaar, Maria van der (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2015)
Kazimierz Twardowski (1866-1938) is the founder of the Lvov-Warsaw School with its strong tradition in logic and its scientific approach to philosophy. Twardowski's unique way of doing philosophy, his method, is of central importance for understanding his impact as a teacher. This method can be understood as a philosophical grammar, which is also how Leibniz conceived his universal language of thought.Analytic philosophy in the twentieth century can be characterized by its opposition to psychologism, on the one hand, and its opposition to metaphysics, on the other. This is changing now, as questions within the philosophy of mind and metaphysics are raised by analytic philosophers today.Maria van der Schaar shows in her book that we can improve our analytic methods by making use of Twardowski's philosophical grammar. Twardowski's positive attitude to psychology and metaphysics may also help us to develop an analytic metaphysics and to get a better understanding of the relation between psychology and philosophy.